Study of Fresh Versus Frozen Embryo Transfer with Reference to Early Pregnancy Loss - Deepti Shrivastava (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Etiology of Increased rate of early abortions associated with pregnancies happened afterIn Vitro Fertilisation are not understood fully till date. ‘Freeze all embryos’ is a new dictum of improvingthe overall success of In Vitro Fertilisation,although it’s effect on early pregnancy loss is controversial inexisting literature .So many studies stated that vitrification and thawing process although improves thepositive pregnancy rate but cause early pregnancy losses after implantion, but other studies contradict it.Hence in present study we wish to find out the difference of early pregnancy demise in frozen thaw embryotransfer cycles in comparison to fresh embryo transfer cycle.Trial Design: This is a cross sectional study which will be conducted in Wardha test tube baby centre,Acharya Vinoba Bhave Rural Hospital.Method: 20 consecutive women conceived after In Vitro Fertilisation, either Fresh or Frozen embryotransfer and will be followed up further for rate of early abortions amongst them.Expected Outcomes: Frozen embryo transfer cycles may have more chances of successful clinicalpregnancies at 6-7 weeks of gestational age, but later on may result in early pregnancy losses.